PERBANDINGAN PENYEMBUHAN RECURRENT APHTOUS STOMATITIS (RAS) MINOR MENGGUNAKAN EKSTRAK LIDAH BUAYA (ALOE VERA) KONSENTRASI 50% DAN 25% - Sari, Ni Nyoman Gemini (Interdental: Jurnal Kedokteran Gigi, 2017)
Minor Recurrent Apthous Stomatitis (RAS) is a recurrent disease in oral mucosa which is commonly occurred. Generally, this disease usually occurred on bucal mucosa, tongue, or floor of the mouth. Aloe vera believed had some roles in accelerate minor RAS healing process because of Aloe vera contains substance that needed in RAS healing process. This study was to figure out the application of 50% Aloe vera extract can heal minor RAS rappidly than the concentration of 25% . There were 30 persons as treated samples which 15 samples applied by 25% a Aloe vera extract and 15 samples applied by 50% Aloe vera extract. The method of this study was experimental with pre-test and post test approach with control group design on the first day and the fifth day. The result of this study was examined with Shapiro Wilk test to know the normality and Levene’s test to know the homogeneity. The mean was analyzed with Paired Sample T-Test and the result was 25% extract t = 2.465 and 50% extract t = 9.068. The conclusion is Aloe vera extract with 50% of concentration can heal minor Recurrent Apthous Stomatitis (RAS) rappidly than 25% of concentration.